2004
DOI: 10.1186/1471-2407-4-65
|View full text |Cite
|
Sign up to set email alerts
|

Methylation profiles of thirty four promoter-CpG islands and concordant methylation behaviours of sixteen genes that may contribute to carcinogenesis of astrocytoma

Abstract: BackgroundAstrocytoma is a common aggressive intracranial tumor and presents a formidable challenge in the clinic. Association of altered DNA methylation patterns of the promoter CpG islands with the expression profile of cancer-related genes, has been found in many human tumors. Therefore, DNA methylation status as such may serve as an epigenetic biomarker for both diagnosis and prognosis of human tumors, including astrocytoma.MethodsWe used the methylation specific PCR in conjunction with sequencing verific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 57 publications
4
49
1
2
Order By: Relevance
“…Loss of expression of CDH13 has been found in parallel with the hypermethylated promoter CpG islands in various cancers (40). However, only one study of gliomas, in which investigation of CDH13 in low grade astrocytomas revealed no methylation patterns, had findings in accordance with our observations (18).…”
Section: G M T a N D R A R β M E T H Y L A T I O N I N H U M A N A supporting
confidence: 80%
See 1 more Smart Citation
“…Loss of expression of CDH13 has been found in parallel with the hypermethylated promoter CpG islands in various cancers (40). However, only one study of gliomas, in which investigation of CDH13 in low grade astrocytomas revealed no methylation patterns, had findings in accordance with our observations (18).…”
Section: G M T a N D R A R β M E T H Y L A T I O N I N H U M A N A supporting
confidence: 80%
“…Furthermore, downregulation of H-cadherin due to hypermethylation in the promoter region of the CDH13 gene appears to be related to the tumorigenesis and invasiveness of these cancers. However, expression of H-cadherin and the methylation status of CDH13 in brain tissue have not been thoroughly investigated (18).…”
Section: Introductionmentioning
confidence: 99%
“…IRF-7 may play a role as a tumor suppressor in its own right because it has been shown to be silenced by hypermethylation in a number of cancer cell lines and tumors (29,38,39) and to be essential for monocyte differentiation (40). It has also been proposed that IRF-7 may play a role in regulating stress response pathways and in the maintenance of genomic stability because it has been observed that IRF-7 can be activated by NH 2 -terminal phosphorylation following DNA damage (41).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour-specific methylation changes in different genes have been identified, [8][9][10][11] and the methylation profile helps us distinguish tumour types and, perhaps, their response to chemotherapeutic agents. 12 Methylation changes are often detected in premalignant or precursor lesions, (before malignant changes) and, thus, may be of use in early detection of cancer.…”
mentioning
confidence: 99%